Impact of Date-Palm Fibers on Fine Soil’s Compaction and Strength Properties (Journal of Engineering, 2024)
This paper investigates the influence of date-palm fibers on the compaction and strength properties of fine soil. The laboratory tests, including specific gravity, compaction tests, and unconfined compression strength tests, were conducted, integrating different proportions (ranging from 0 to 2%) of date-palm fibers into the soil mixture. The palm fibers were divided into two distinct lengths (30 mm and 60 mm) to be mixed with the soil. Nine samples were prepared with varying proportions of date-palm fibers for the experimental investigation, aiming to specifically examine the influences exerted by both palm-fiber length and palm-fiber content on the soil's compaction and strength characteristics when mixed with date-palm fibers. The compaction test results demonstrate a decrease in the dry unit weight and an increase in the optimum moisture content by approximately 10%. Additionally, the length of the date-palm fibers impacts the optimum moisture content and the maximum dry unit weight of the soil mixture. In contrast, the unconfined compressive stress increased by about 30% with higher date-palm fiber contents. This increase in unconfined compressive stress due to increased date-palm fiber content is a significant finding, indicating improved soil strength. This finding holds the enhancing construction performance, sustainability, and cost-efficiency. In conclusion, this soil-fiber mixture shows suitable hydraulic applications. The utilization of natural materials in civil engineering demands the exploration of available natural fibers.